Severe cardiomyopathy revealing antineutrophil cytoplasmic antibodies‐negative eosinophilic granulomatosis with polyangiitis. Issue 9 (September 2014) - Bouiller, K.; Samson, M.; Eicher, J.‐C.; Audia, S.; Berthier, S.; Leguy, V.; Humbert, O.; Martin, L.; Lorgis, L.; Cottin, Y.; Bonnotte, B.; Lorcerie, B.
Abstract Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare form of systemic vasculitis in which cardiac involvement is frequent and severe, and accounts for half of EGPA‐related deaths. ANCA‐positive EGPA differs from ANCA‐negative EGPA in that the former is significantly associated with renal involvement, peripheral neuropathy and biopsy proven vasculitis, whereas the latter is associated with cardiac involvement. Herein, we report a case of EGPA with myocarditis in a woman, who was successfully treated with steroids and cyclophosphamide. This report highlights the importance of diagnosing cardiac involvement in EGPA early, especially in ANCA‐negative patients.